An examination of the extent of participation by non-governmental organisations (NGO's) in the legislative process of the KwaZulu-Natal legislature - Schoeman, Maxi (University of Pretoria, 2013)
Dissertation (MA (Political Policy Studies))--University of Pretoria, 2007.